Sushi Reverses Course: Consuming American Sushi in Tokyo - Matthew Allen; Rumi Sakamoto (Asia-Pacific Journal, 2011)
Sushi, not long ago a quintessentially Japanese product, has gone global. Japanese food, and sushi in particular, has experienced a surge in international popularity in recent decades. Japanese government estimates that outside of Japan there are over 20,000 Japanese restaurants, most of which either specialize in sushi or serve sushi (MAFF 2006; Council of Advisors 2007).1 Some estimate the number of overseas sushi bars and restaurants to be between 14,000 and 18,000 (in comparison, the number of sushi restaurants in Japan is estimated to be around 45,000) (Matsumoto 2002: 2). Sushi stores today can be found across Asia, the Americas, Europe, Russia, Africa, Oceania and the Pacific. The phenomenon has accelerated rapidly since the turn of the millennium.While sushi’s global expansion has attracted the attention of Japanese and global media (Kato 2002; Matsumoto 2002; Tamamura 2004; Ikezawa 2005; Fukue 2010) and a number of scholarly works address sushi’s global popularity and its transformation outside Japan (Bestor 2000; Ng 2001; Cwiertka 1999; 2005; 2006),2 little scholarly or journalistic work exists on one important facet of sushi’s recent global growth — namely, the return home of transformed sushi to Japan, at times in barely recognisable forms. This paper offers an analysis of this “reverse import (gyaku yunyū)” phenomenon and its specific expression in what we refer to as “American sushi” in Tokyo as a contribution toward assessing culinary globalisation. The nascent American sushi trend brings into relief aspects of Japan-US relations that are seldom articulated in the context of discourse about food – in particular the continued symbolic dominance of the US in Japanese eyes;3 and it also is emblematic of how Japan engages aspects of globalisation, in this case fetishising a mundane product that has become something new in its reimported form. By focusing on this relatively recent phenomenon we also aim to contribute to and complicate the contemporary arguments that characterise cultural globalisation as a unilineal process of hybridisation, often through localisation.Using the cases of two high profile “American” sushi restaurants in Tokyo, we show that the Japanese reflexive consumption of “America” demonstrates that the sign of otherness remains a significant factor in framing domestic consumption. The return “home” of the transformed product that is at once both familiar and exotic occupies a different symbolic space to the ideas formalised in the so-called “McDonaldisation” (Ritzer 1993) of global production, which dominates much of the thinking about globalisation of culture. While McDonaldisation may entail efficient, standardised and controlled forms of cultural hybridisation such as the teriyaki chicken burger, American sushi in Tokyo presents a different type of hybridisation characterised by the playfulness and unpredictability of its production and consumption. To draw this point out, we employ the concept of “fetish” and offer a reading of cultural globalisation that is not just about products expanding out from a centre to the periphery where they are modified, but is also about producing and consuming a fetishised object of desire that has accumulated extra social and symbolic capital (Bourdieu, 1977) as it has crossed and re-crossed national borders. As we will see, the marketability and desirability of American sushi in Japan comes primarily from its symbolic (that is, fetishised) value (we will discuss this in some detail later).Before examining American sushi, however, it is important to locate this phenomenon within the historical context of sushi both in Japan and its expansion to the rest of the world, especially to the United States.